Functional Reading Activities to Motivate and Empower for Young Adults With Intellectual or Developmental Disabilities: A Randomized Pilot Trial - Prahl, Alison; Fraze, Kaitlynn; Kannan, Anupama; Grauzer, Jeffrey; Sturdivant, Rodney X (American journal of speech-language pathology, 2025)
Reading proficiency is an important life skill that contributes to improved quality of life and becoming an active member in society. This pilot randomized clinical trial tested the effects of a functional literacy intervention in young adults with intellectual and/or developmental disabilities (IDDs). Participants included 44 young adults with IDD between 18 and 26 years old. Participants were randomly assigned to the Functional Reading Activities to Motivate and Empower (FRAME) treatment group or a "business-as-usual" control group. Participants participated in 24 twice-weekly sessions in which they were taught reading comprehension strategies in the context of functional text stimuli or activities of daily living that require reading (e.g., text messages, e-mails). The primary outcome measure was the number of reading comprehension strategies used. Secondary outcomes included (a) multiple-choice comprehension questions, (b) text message response, (c) e-mail response, (d) summarization, and (e) verbal responses to functional text samples. Young adults with IDD in the treatment group made statistically significant gains in use of reading comprehension strategies ( = 1.09, = .002) and multiple-choice comprehension questions ( = 0.79, = .038) as compared with the control group. There were no statistically significant differences on the remaining outcome measures. This study provides preliminary support for the short-term effects of the FRAME intervention for young adults with IDD, with particular emphasis on explicit reading comprehension strategy instruction within a functional context. Therapeutic services typically end during the transition period for young adults with disabilities. However, it is essential that evidence-based literacy supports are available as this is a skill that continues to develop throughout the lifespan and has the potential to transform an individual's transition to adulthood and independence. Future research should include a larger clinical trial and evaluate mediators of intervention effects.